Characteristics of food consumption during the Covid-19 pandemic among residents of the metropolitan region of Belém (International Seven Journal of Health Research, 2023)
INTRODUCTION: Food is important for a healthy life, it should be varied and of nutritional quality. In view of this, a research was developed addressing dietary variables of residents of the metropolitan region of Belém, Marabá and Santarém during the first peak of the new coronavirus pandemic. OBJECTIVES: To observe the participants' eating practices from March to August 2020. METHODOLOGY: The present study was a research project developed by the Academic League of Collective Health and Parasitology, of the UNINASSAU University Center, where the electronic form (Google forms) was used in which the participants (over 18 years old) answered objective questions related to the pandemic period, mainly about the food consumed. This study was approved by the CEP of the Evandro Chagas Institute on 08/21/2020 with opinion No. 4,229,578. RESULTS AND DISCUSSION: With social isolation, 89.8% of the 275 respondents reported a decrease in trips to supermarkets. Regarding the change in food consumption, it was observed: 33.1% stated that they had not changed their eating habits, 18.5% were consuming a greater amount of processed foods, 23.3% were consuming industrialized and natural foods, and 25.1% were consuming a greater amount of natural foods, which is positive, as these foods contribute to the strengthening of the immune system. In addition, the frequency of consumption of certain foods was addressed, in which there was a higher percentage for fruits and vegetables with 62.5% and 59.6%, respectively. However, a significant value was for pasta (46.9%) and sweets (38.5%). CONCLUSION: The changes reported by the participants show a qualitative improvement in the diet from the increase in the consumption of fruits and vegetables, but accentuated percentages of the consumption of pasta and sweets coexist.